The Distribution Characteristics of GPS Cycle Slip Over the China Mainland and Adjacent Region During the Declining Solar Activity (2015–2018) Period of Solar Cycle 24. Issue 5 (6th May 2021) - Geng, Wei; Huang, Wengeng; Liu, Guoqi; Liu, Siqing; Luo, Binxian; Chen, Yanhong
Abstract: The Global Positioning System (GPS) cycle slip has a marked impact on the application of communication and navigation systems and therefore is one of the main concerns of the user and designer of terminal systems. In this study, we analyzed the temporal and spatial characteristics of cycle slip events using the GPS data detected from 260 observations in the China sector during the period of the year 2015–2018. The results show that the temporal variations of cycle slips are dependent on the local time, seasons, and solar activity. It occurs from 20:00 LT to midnight and more frequently in the equinox months, especially in solar maximum years. The spatial distribution occurs mainly at southern sector below 25°N, which should be associated with the solar condition and ionospheric irregularities in the equatorial region, and the case analyses reveal that the variation of cycle slips has a similar tendency with the ionospheric scintillation monitored at low‐latitude station Guangzhou explaining this relationship. Our results reflect the performance of the GPS signals monitored in the China area during the declining period of solar activity to some degree. Plain Language Summary: The cycle slip is one of the main impacts on communication and navigation systems and is also the main concern of space weather researches. To understand the distribution characteristics of the cycle slip over China mainland and adjacent region, we detect it using a specialized method and analyze the results of the cycle slip event. We find that the cycle slips are dependent on the local time, seasons, solar activity, and latitude. The cycle slip occurs in solar maximum years much more frequently. In solar maximum years, cycle slips occurrence more frequently in the equinox months than in other months and mainly occurs from 20:00 LT to midnight. The spatial distribution results indicate that most cycle slip events occur in the southern sector (below 25° at latitude). Moreover, we analyze the relationship between cycle slip and solar activity and ionospheric scintillation, and it is important to understand because the China longitudinal sector is one interesting transitional zone where the scintillation event is active. This study can contribute to space weather researchers and GNSS users to analyze the characteristics of the cycle slips, and is also used to evaluate the ionospheric effect on GPS to improve positioning performance in GPS application. Key Points: The temporal and spatial characteristics of cycle slips are analyzed using the GPS data detected from almost 260 observations in the China sector during the period of the year 2015–2018 The variations of cycle slip are dependent on the local time, seasons, solar activity, and latitudes The feature of cycle slip occurrence is related to the solar activity and distribution of ionospheric scintillation above a certain intensity level over the China region